Blood-based detection of MMP11 as a marker of prostate cancer progression regulated by the ALDH1A1-TGF-β1 signaling mechanism - Ielizaveta Gorodetska; Vasyl Lukiyanchuk; Marta Gawin; Myroslava Sliusar; Annett Linge; Fabian Lohaus; Tobias Hölscher; Kati Erdmann; Susanne Fuessel; Angelika Borkowetz; Anna Wojakowska; Daniel Fochtman; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Prostate cancer (PCa) is the second most common type of tumor diagnosed in men and the fifth leading cause of cancer-related death in male patients. The response of metastatic disease to standard treatment is heterogeneous. As for now, there is no curative treatment option available for metastatic PCa, and the clinical tests capable of predicting metastatic dissemination and metastatic response to the therapies are lacking. Our recent study identified aldehyde dehydrogenases ALDH1A1 and ALDH1A3 as critical regulators of PCa metastases. Still, the exact mechanisms mediating the role of these proteins in PCa metastatic dissemination remain not fully understood, and plasma-based biomarkers of these metastatic mechanisms are not available. Methods Genetic silencing, gene overexpression, or treatment with different concentrations of the retinoic acid (RA) isomers, which are the products of ALDH catalytic activity, were used to modulate the interplay between retinoic acid receptors (RARs) and androgen receptor (AR). RNA sequencing (RNAseq), reporter gene assays, and chromatin immunoprecipitation (ChIP) analysis were employed to validate the role of RARs and AR in the regulation of the transforming growth factor-beta 1 (TGFB1) expression. Gene expression levels of ALDH1A1, ALDH1A3, and the matrix metalloproteinase 11 (MMP11) and their correlation with pathological parameters and clinical outcomes were analysed by mining several publicly available patient datasets as well as our multi-center transcriptomic dataset from patients with high-risk and locally advanced PCa. The level of MMP11 protein was analysed by enzyme-linked immunosorbent assay (ELISA) in independent cohorts of plasma samples from patients with primary or metastatic PCa and healthy donors, while plasma proteome profiles were obtained for selected subsets of PCa patients. Results We could show that ALDH1A1 and ALDH1A3 genes differently regulate TGFB1 expression in a RAR- and AR-dependent manner. We further observed that the TGF-β1 pathway contributes to the regulation of the MMPs, including MMP11. We have confirmed the relevance of MMP11 as a promising clinical marker for PCa using several independent gene expression datasets. Further, we have validated plasma MMP11 level as a prognostic biomarker in patients with metastatic PCa. Finally, we proposed a hypothetical ALDH1A1/MMP11-related plasma proteome-based prognostic signature. Conclusions TGFB1/MMP11 signaling contributes to the ALDH1A1-driven PCa metastases. MMP11 is a promising blood-based biomarker of PCa progression.